Differences in the Effects of Strengthening on Bosu and Activity-Based Exercises on Hallux Valgus Pain - Pratiwi, Agesti Setiya; Ramadhani, Alinda Nur; Mutnawasitoh, Asita Rohmah; Mirawati, Dita (FISIO MU: Physiotherapy Evidences, 2026)
Introduction: Hallux valgus is a deformity of the first toe characterized by outward bending due to a valgus position at the metatarsophalangeal joint. This deformity can cause pain and interfere with daily activities, especially among working women. To determine the difference in the effects of Strengthening on bosu and Activity-Based Exercises on reducing pain caused by hallux valgus in working women in Bulakrejo Village. Methods: This study used a quasi-experimental two-group with a pre-test and post-test design. The sample consisted of 50 subjects divided into two intervention groups with randomization. Pain was measured using the Visual Analog and Numeric Rating Scale (VANRS). Both interventions were conducted for four weeks, three times per week. Data were analyzed using the Wilcoxon test to examine the effect of each intervention and the Mann-Whitney test to compare differences between groups. Results: Strengthening on bosu significantly reduced pain (p=0.001; CI=95%) and activity-based exercise also significantly reduced pain (p=0.001; CI=95%) in working woman with hallux valgus. However, there was a significant difference between the groups (p=0.014), with a greater effect on strengthening on bosu. Conclusion: Both methods are effective in reducing pain, but there is a difference in impact between the two, strengthening on bosu has more effect than activity-based exercise.